2021
DOI: 10.1063/5.0052189
|View full text |Cite
|
Sign up to set email alerts
|

Scaling theory of three-dimensional magnetic reconnection spreading

Abstract: We develop a first-principles scaling theory of the spreading of three-dimensional (3D) magnetic reconnection of finite extent in the out of plane direction. This theory addresses systems with or without an out of plane (guide) magnetic field, and with or without Hall physics. The theory reproduces known spreading speeds and directions with and without guide fields, unifying previous knowledge in a single theory. New results include the following: (1) reconnection spreads in a particular direction if an x-line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Most of the previous theoretical and numerical work on the spreading of reconnection has addressed quasi-2D anti-parallel reconnection in uniform current sheets with an initial half-thickness w 0 comparable to the ion inertial scale d i = c/ω pi , where c is the speed of light in vacuum and ω pi is the ion plasma frequency. The consensus is that reconnection spreads orthogonal to the reconnection plane with the velocity of the current carriers (Huba & Rudakov, 2002Shay et al, 2003;Karimabadi et al, 2004;Lapenta et al, 2006;Shepherd & Cassak, 2012; T. K. M. Nakamura et al, 2012;Meyer III, 2013;Jain et al, 2013;Jain & Büchner, 2017;Arencibia et al, 2021). This directionality of the spreading is consistent with observations of reconnection during substorms, which spread in the dawnward direction (McPherron et al, 1973;Nagai, 1982;Nagai et al, 2013).…”
Section: Introductionsupporting
confidence: 67%
“…Most of the previous theoretical and numerical work on the spreading of reconnection has addressed quasi-2D anti-parallel reconnection in uniform current sheets with an initial half-thickness w 0 comparable to the ion inertial scale d i = c/ω pi , where c is the speed of light in vacuum and ω pi is the ion plasma frequency. The consensus is that reconnection spreads orthogonal to the reconnection plane with the velocity of the current carriers (Huba & Rudakov, 2002Shay et al, 2003;Karimabadi et al, 2004;Lapenta et al, 2006;Shepherd & Cassak, 2012; T. K. M. Nakamura et al, 2012;Meyer III, 2013;Jain et al, 2013;Jain & Büchner, 2017;Arencibia et al, 2021). This directionality of the spreading is consistent with observations of reconnection during substorms, which spread in the dawnward direction (McPherron et al, 1973;Nagai, 1982;Nagai et al, 2013).…”
Section: Introductionsupporting
confidence: 67%
“…The strength of the normal magnetic field component B y near the reconnection region is an indicator of the presence of reconnection (Arencibia et al, 2021;Huba & Rudakov, 2002;Jain & Büchner, 2017;Li et al, 2020). The average magnitude of B y at the left and right downstream edges of the electron diffusion region is a proxy for the reconnection rate; we denote this quantity as 𝐴𝐴 B𝐵𝑦𝑦(𝑧𝑧𝑧 𝑧𝑧) , given by…”
Section: Resultsmentioning
confidence: 99%
“…In a small interval of time Δ t , B y propagates a distance Δ z in the z direction, and the spreading speed is defined as v s = Δ z /Δ t . It is estimated from a scaling analysis of Equation , giving vscnormalΔExnormalΔBy. ${v}_{s}\sim -c\frac{{\Delta }{E}_{x}}{{\Delta }{B}_{y}}.$ For anti‐parallel reconnection, it was argued that the main contributor to E x is the Hall electric field − J z B y / nec (Arencibia et al., 2021), where n is the upstream density and e is the elementary charge, so that vscnormalΔ()JzBy/necnormalΔBy. ${v}_{s}\sim c\frac{{\Delta }\left({J}_{z}{B}_{y}/nec\right)}{{\Delta }{B}_{y}}.$ For a current sheet of uniform thickness, J z and n are independent of z , so Equation becomes vsJzne. ${v}_{s}\sim \frac{{J}_{z}}{ne}.$ This result provided a first‐principles scaling prediction of the previously known result that spreading of anti‐parallel reconnection in a current sheet of uniform thickness occurs at the speed of the current carriers (Huba & Rudakov, 2002, 2003; Jain et al., 2013; Shay et al., 2003). Since J z ∼ cB 0 /4 πw , Equation gives vscB04πnewcA0diw, ${v}_{s}\sim \frac{c{B}_{0}}{4\pi new}\sim \frac{{c}_{A0}{d}_{i}}{w},$ where di=c/ωpi=mic2/4πne21/2 ${d}_{i}=c/{\omega }_{pi}={\left({m}_{i}{c}^{2}/4\pi n{e}^{2}\right)}^{1/2}$ is th...…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…PIC models have shown reconnection to spread at slower rates when the current sheet is thicker (Li et al., 2020). Thick current sheets in night‐side PIC models are used to confine reconnection extent (Liu et al., 2019), although it has been shown that simulation size can affect spreading properties of varying current sheet thickness in a two‐fluid code (Arencibia et al., 2021).…”
Section: Reconnection Spatial Limitationsmentioning
confidence: 99%